Antidepressant and anxiolytic effects of melalueca cajuputi essential oil in chronic immobilisation stress (CIS)-induced mice model - Noor, Muhamad Arif Azimi Md (2021)
Depression and anxiety are common mental disorders that occurred due to monoamine neurotransmitter imbalance. Current available therapies are less effective and produce several side effects, thus requiring alternative treatment approaches. From the preliminary study, the phytochemical compounds in Melalueca cajuputi essential oil (MCEO) possessed antidepressant (43.6%) and anxiolytic (34.3%) properties. This study was conducted to evaluate antidepressant and anxiolytic effects of MCEO in chronic immobilisation stress (CIS) - induced mice. Sixty-four males Swiss albino mice were divided into eight groups randomly (n=8) that comprised of control and treatment groups. The control groups consisted of normal control, negative control and positive control amitriptyline (20 mg/kg), while treatment groups were divided according to five different MCEO concentrations (1%, 2.5%, 5%, 7.5% and 10% v/v). The mice groups except the normal group were induced with CIS procedure for 2 hours everyday for 15 consecutive days. Freshly prepared MCEO was dissolved in 1% dimethyl sulfoxide (DMSO) and 0.9% saline, before the experiment. All mice in the treatment group were treated with MCEO via inhalation and amitriptyline (20 mg/kg) via intraperitoneal route on day 16 until day 21. The antidepressant and anxiolytic effects were evaluated via forced swimming test, elevated plus maze test, changes of granular cell layer (GCL) and pyramidal cell layer (PCL) surface areas and corticotrophin releasing hormone (CRH) level on day 21 respectively. The test results were analysed by using one-way ANOVA followed by Dunnet’s post-hoc test with significant level at p<0.05. MCEO at 1% 2.5%, 5%, 7.5% and 10 % v/v significantly reduced depression-like behaviours while at 5%, 7.5% and 10 % v/v significantly reduced anxiety-like behaviours in the CIS-induced mice compared to the negative control group. The mice body weights were significantly increased (p<0.05) in the MCEO treatment groups of 5%, 7.5% and 10% v/v. Besides, there were significant increase (p<0.05) in the GCL and PCL surface areas at MCEO concentrations of 7.5% and 10% v/v. CRH blood level in the mice was found to be reduced significantly following treatment with MCEO at all tested concentrations. In conclusion, MCEO at concentration of 7.5% v/v is the most effective concentration that exhibits antidepressant and anxiolytic effects in mice that induced with CIS. MCEO exhibits antidepressant and anxiolytic effects probably due to phytochemical contents that regulate the CRH pathway that lead to increased of GCL and PCL surface areas. The data of this study can be used as guideline for future clinical study.